Effects of parent-child physical activity intervention on gross motor skills among preschoolers in Shanxi province, China - Zhao, Jia (2024)
Gross motor development is fundamental for young children to developing the advanced movement and specific skills. Parents are children’s first teachers who can support their physical and mental growth development. However, physical activity levels in young children are low in China, the efficient and effective parent-child physical activity interventions to increase physical activity in young children are unclear. The purpose of this quantitative study was to investigate the effect of parentchild physical activity intervention on children’s gross motor skills. A total of 66 children aged five to six and their parents from Changzhi city in China were divided into two group to participate in the experimental parent-child physical activity intervention program in this study. Two instruments including Children’s Family Physical Education Environment Questionnaire and the Test of Gross Motor Development-2 were used in the pre-test and post-test of experiments. The findings show that parent-child physical activity intervention program, had a significant effect on children’s gross motor skills. After parent-child physical activities intervention, parents’ attitude towards children’s physical education had relationship with children’s gross motor skills intervention. While the relationship between sports materials at home before and after in treatment group were not found. The findings indicated that it is necessary for parents to provide opportunities for their children to engage in physical activity that promote a diversity of motor skills. Parents need to improve their attitudes of physical education, provide enrich sports materials and company their child to engage in physical activity in home environment to help their child to improve gross motor skills in their daily life.